Temporary Extensions and Modifications Of Access Limits In The Fund's Lending Facilities. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2021)
The Fund introduced two main sets of temporary adjustments to its lending frameworks in the early months of the pandemic: (i) increases in the limits on access to its emergency financing instruments (April 2020) and (ii) increases in the annual limits on access to financing from both its general and concessional financing facilities (July 2020).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet